Knowledge Management System Usage and Organization Learning: Recent Trends and Open Problems - FITRIASTUTI, Lucia Ika; SUJOKO, Sujoko; HERAWAN, Tutut; VEMBERI, Yohannes (Journal of Advanced Research in Law and Economics, 2019)
Knowledge management system and organizational learning are now increasingly popular and receiving much attention from organizations. Knowledge management system and organizational learning are important assets that could support the achievement of organizational goals. The objective of this article is to review and present a comprehensive review of the latest research related to knowledge management systems and organizational learning related to innovation and organizational performance. This article analyzes previous studies conducted in 1995 to 2018 (51 references) in terms of the research methods, advantages and limitations. The analysis results bring up issues and opportunities for future research related to knowledge management system and organizational learning. This article will help future researchers in finding interesting ideas to develop both theories and methodologies relation to future conditions. Besides, this article will provide more information and knowledge for organizations in implementing knowledge management systems and organizational learning.